2004
DOI: 10.1136/jnnp.2003.028761
|View full text |Cite
|
Sign up to set email alerts
|

Mucuna pruriens in Parkinson's disease: a double blind clinical and pharmacological study

Abstract: Background: The seed powder of the leguminous plant, Mucuna pruriens has long been used in traditional Ayurvedic Indian medicine for diseases including parkinsonism. We have assessed the clinical effects and levodopa (L-dopa) pharmacokinetics following two different doses of mucuna preparation and compared them with standard L-dopa/carbidopa (LD/CD). Methods: Eight Parkinson's disease patients with a short duration L-dopa response and on period dyskinesias completed a randomised, controlled, double blind cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
151
0
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(165 citation statements)
references
References 39 publications
6
151
0
8
Order By: Relevance
“…In a clinical study, Nagashayana et al (2000) revealed the contribution of L-DOPA in the recovery of PD followed by Ayurveda medication. Katzenschlager et al (2004) revealed that 30 g Mucuna seed powder preparation has considerable faster action in treating PD patients than conventional standard drugs, namely, Levodopa or Carbidopa and suggested that natural source of L-DOPA might possess advantages over conventional drugs in long term management of PD.…”
Section: Anti-parkinson's Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In a clinical study, Nagashayana et al (2000) revealed the contribution of L-DOPA in the recovery of PD followed by Ayurveda medication. Katzenschlager et al (2004) revealed that 30 g Mucuna seed powder preparation has considerable faster action in treating PD patients than conventional standard drugs, namely, Levodopa or Carbidopa and suggested that natural source of L-DOPA might possess advantages over conventional drugs in long term management of PD.…”
Section: Anti-parkinson's Activitymentioning
confidence: 99%
“…It is used against a wide range of disorders, such as urinary tract, neurological and menstruation disorders, constipation, edema, fever, tuberculosis, ulcers, PD (Katzenschlager et al, 2004) and helminthiases like elephantiasis (Oudhia, 2002). Traditionally, the powdered seeds of M. pruriens was found to increase the general mating behavior and thereby sexual activity in rats (Amin et al, 1996).…”
Section: Traditional Usesmentioning
confidence: 99%
“…DA content in the cortex with no significant effect on levodopa, norepinephrine or DA, serotonin and their metabolites. The failure of M. pruriens endocarp to significantly affect DA metabolism in the striatonigral tract along with its ability to improve Parkinsonian symptoms in the 6-hydroxydopamine animal model and humans may suggest that its anti-Parkinson's effect may be due to components other than levodopa or that it has a levodopaenhancing effect (37 min) (Katzenschlager et al, 2004;Manyam et al, 2004).…”
Section: Femalementioning
confidence: 99%
“…[24] An n-propanol extract of M. pruriens seeds yields the highest response in neuroprotective testing involving the growth and survival of DA neurons in culture. Interestingly, n-propanol extracts, which contain a negligible amount of L-DOPA, have shown significant neuroprotective activity, suggesting that a whole extract of M. pruriens seeds could be superior to pure L-DOPA with regard to the treatment of Parkinsonism.…”
Section: Antioxidant Activitymentioning
confidence: 99%